PEMECAHAN MASALAH SYARAT BATAS DUA TITIK (SOLVABILITY OF TWO POINT BOUNDARY VALUE PROBLEMS) - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Etektro dan Teknotogi Informasi Universitas Gadjah Mada, 2000)
ABSTRACT The boundary value problems can solve various complicated problems. If mathematical model assumes on theoretical frame work and ability to communicate model, so the boundary value problems operate based on the concept and potency of differential equations related to the various boundary, simulation and estimation for optimizing that condition in industrial sector and economy development. Various industries can be represented, engineered or solved through differential equations, for example automotive industry and others physical phenomena. In this case boundary value problems are very important for science and technology, particulary on construction and engineering, beside application on biology, chemistry, ecology and social sciences. Such advance, can only be achieved by having a research on the basic science, one branch of mathematics which is very important to be developed is boundary value problems. In this paper is discussed the existence of solution of two point boundary value problems for second order differential equations of the form : x" = f(t,x,x'), t E [0,1] , where f :[0,1] x 912-* 91 is continuous, and x(t) satisfies the boundary conditions to connected of two points : x(0)=A, x1(1)=B